PERAN KOPERASI PRODUSEN USAHA KARYA BERSAMA D ALA M UP AY A M E NI NG KAT KA N KEMAMPUAN EKONOMI ANGGOTA MENURUT EKONOMI ISLAM - Burhanuddin Burhanuddin; Sri Deti, Nashirun (ADISAM PUBLISHER, 2024)
This study is based on the phenomenon that the cooperative producer of joint work business is a form of cooperative that establishes a partnership with PT. Fajar Saudara Lestari in order to distribute and share the results of palm oil production. The Joint Work Business Cooperative (UKB) receives payments or fees from the Company at a rate of 1% of the total sales value of Fresh Fruit Buns (FFB) each month. It can be concluded that the cooperative earns a fairly large income every month, however, the funds are only distributed to members according to the agreement that has been regulated in the cooperative regulations. The focus of this study is 1) What is the role of the Joint Work Business Producer Cooperative in improving the economic capacity of its members? 2) What are the efforts to improve the economic capacity of members of the Joint Work Business Producer Cooperative according to Islamic economics? This study uses a qualitative approach and a Descriptive type. Data collection techniques through observation, interviews, and documentation studies. Data analysis uses an interactive model that includes data reduction, data display and data verification or drawing conclusions. The results of the study The role of cooperatives in improving the welfare of members can be marked by an increase in the income of its members. The role of the Karya Bersama Business Producer Cooperative in improving the economic capacity of its members is through a mutual assistance system (ta'awun), without interest and without fines on the savings and loan system. Then, efforts to improve the economic capacity of members of the Karya Bersama Business Producer Cooperative according to Islamic Economics are by establishing cooperation in a network of work partners with the palm oil company PT. Fajar Saudara Lestari so that they get a fee from the cooperation which is distributed to members so that it can help increase income or the economy. The practice of the Karya Usaha Producer Cooperative is in accordance with the principles of Islamic Economics.